Tai Chi as a Body-Mind Exercise for Promotion of Healthy Aging in Nursing Home Residents: Appropriateness, Feasibility, and Effectiveness - Lee LYK; Chu ECP (Clinical Interventions in Aging, 2023)
Linda Yin-King Lee,1,* Eric Chun-Pu Chu2,* 1School of Nursing and Health Studies, Hong Kong Metropolitan University, Hong Kong, People’s Republic of China; 2New York Chiropractic and Physiotherapy Centre, EC Healthcare, Hong Kong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Linda Yin-King Lee, School of Nursing and Health Studies, Hong Kong Metropolitan University, Ho Man Tin, Kowloon, Hong Kong, People’s Republic of China, Tel +852 3970 8702, Fax +852 2406 2375, Email leeyinking@gmail.comAbstract: The lack of activity, opportunity for providing input and participation in activities, and interaction with other people are the features of institutional living which reinforces dependency among nursing home residents. Residents are usually frustrated with paternalistic-type care. Arranging health-oriented meaningful activities for residents contributes to health promotion and enhancement of healthy aging. Moreover, it contributes to the cultivation of a positive meaning of life which is particularly important as residents reach the late geriatric stages of their lives. With exercise being seen as generally beneficial for health, Tai Chi as a Chinese-based exercise with a body-mind emphasis and unique characteristics becomes a particularly suitable exercise in aiding the residents in this major shift of lifestyle. This paper analyzes the appropriateness, feasibility, and effectiveness of Tai Chi in promoting healthy aging for residents. Theoretical considerations and scientific evaluations lend it appropriate, feasible, and effective in providing physiological and psychosocial health benefits to the residents. This paper recommends the use of Tai Chi to promote healthy aging in nursing home residents. With a rapidly aging population and mounting demand for residential geriatric care worldwide, this paper’s timely findings should provide important implications for adopting Tai Chi to advance the quality of care delivered by nursing homes worldwide.Keywords: Tai Chi, exercise, healthy aging, nursing homes, long-term care